A Note on Stability of an Operator Linear Equation of the Second Order - Janusz Brzdȩk; Soon-Mo Jung (Abstract and Applied Analysis)
We prove some Hyers-Ulam stability results for an operator linear equation of the second order that is patterned on the difference equation, which defines the Lucas sequences (and in particular the Fibonacci numbers). In this way, we obtain several results on stability of some linear functional and differential and integral equations of the second order and some fixed point results for a particular (not necessarily linear) operator.